Bioprospecting of Halotolerant Bacterial Isolates for Potassium Recovery from K‐Feldspar. Issue 9 (16th August 2016) - Bachani, Pooja; Bhattacharya, Sourish; Jain, Deepti; Patidar, Shailesh Kumar; Soundarya, Rajapitamahuni; Tirkey, Sushma Rani; Ranawat, Bablesh; Bharadwaj, S. V. Vamsi; Mishra, Sandhya
Abstract: Potassium‐solubilizing bacteria were isolated from solar salt pans of an experimental salt farm and Sambhar Lake, mining areas of Naseerabad, and wastewater from a marble cutting machinery. Seven promising bacterial isolates from Makrana, three from Sambhar Lake, and three from Naseerabad were found to have comparatively better potassium‐solubilizing capacity. Out of these, three potential bacterial isolates were identified as Acinetobacter soli (MTCC 5918), Enterobacter xiangfangensis (MTCC 5917), and Acinetobacter baumannii (MTCC 5916). A. soli was found to have maximum potassium‐releasing capacity in the supernatant which may be further applied as a biofertilizer. Abstract : The use of potassium‐solubilizing bacteria may be economically important with combined use of K‐feldspar which can increase the K availability to crops and enhance the growth of plants for sustainable, evergreen agriculture replacing commonly used chemical fertilizers. Three potential halotolerant bacterial isolates were selected with different biochemical characteristics.